Active conductances in motoneuron dendrites enhance movement capabilities - Heckman, C. J. (Exercise and Sport Sciences Reviews, 2003)
Synaptic input to motoneurons was traditionally thought to flow passively from the dendrites to the soma and initial axon segment. It is now clear that voltage-sensitive channels in motoneuron dendrites can generate large active currents, which are influenced by neuromodulators that are released by brainstem neurons. These neuromodulators may be essential for generating large forces.